The use of technology by women gari producers in Bamunkumbit village, Northwest Region of Cameroon - LENGHA, TOHNAIN Nobert (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Cassava is one of the main starchy staple foods in Cameroon with 80% of rural and urban households consuming it and its other derivatives daily. The increase in demand for this tuber and its proceeds has led to increased prices because of high demand and consequently leading to an increase in production exceeding the previous traditional subsistence systems. Women rely mostly on traditional techniques to produce one of its by-products known as gari. This study focuses on the adoption of Agricultural Technology Transfer by women gari producers in Bamunkumbit North West Region of Cameroon and the efficiency of the adoption of the new technology. The factors identified as having direct impact on women producers towards adoption of appropriate technology are educational level, marital status, and access to funding for production. Data was collected with the use of questionnaire, and focus group discussion (FGD) guides. Results indicate that most rural women are eager to adopt improved technology but are hindered by their level of education and the absence of farm to market roads which is a general problem affecting the country. It is equally obvious from the results that no modern technology could be adopted except through the valorization of the existing technological approaches.